Serious “human papillomavirus vaccine” game for Malaysian adolescents : Development and preliminary study - Nur Hazreen, Mohd Hasni; Akmal Asyraf, Mior Azalian; Tuty Asmawaty, Abdul Kadir; Mohd Azrul Hisham, Mohd Adib (Intelektual Pustaka Media Utama, 2023)
In Malaysia, cervical cancer is the top three most common cancer among women. Vaccination and screening are mandatory for the prevention of the disease. Therefore, we aimed to develop a serious game for Malaysian adolescents, the "HPV Vaccine” game objectively to transmit knowledge about human papillomavirus (HPV), create awareness of cervical cancer, and promote HPV vaccine uptake. This game development targeted teenagers aged 10 to 17 years. We expect to complete three levels and answer all 15 questions. Inclusion criteria were Malaysian citizens, who owned a computer with connectivity to the game. We excluded those with a physical disability. This game was the first edutainment on Human papillomavirus, cervical cancer, and the HPV vaccine. We conducted a preliminary study, cross-sectionally, purposive sampling method. We recruited 20 participants; only 16 participants consented and completed the study. All participants enjoyed the wireframes of the game, with an average of 12 to 15 minutes to complete the game. Results demonstrate that participants were highly engaged with the “HPV Vaccine” game. We believe this game, is a forward technology that will beneficial for adolescents' adherence to HPV vaccination. In the future, we suggest an observational study to assess players' perspectives on this game.